Calorimetry in particle physics : (World Scientific, 2005)
The International Conference on Calorimetry in Particle Physics is the major and most comprehensive forum for discussion on state-of-the-art developments of calorimetry technologies. The Eleventh Conference covered all aspects of calorimetric detection and measurements, with emphasis on high energy physics and astrophysics experiments. Besides the usual discussion on calorimetry technologies this edition is enriched by the presence of two sections dedicated to new techniques for calorimetry and applications to calorimetry for the next Linear Collider experiments.